2019
DOI: 10.1542/peds.2018-2218
|View full text |Cite
|
Sign up to set email alerts
|

Improving Care for Sickle Cell Pain Crisis Using a Multidisciplinary Approach

Abstract: OBJECTIVES: Frequent hospitalizations for sickle cell disease (SCD) vaso-occlusive crises (VOCs) are associated with school absenteeism, emotional distress, and financial hardships. Our goal was to decrease hospital days for VOC admissions by 40% over a 5-year period. METHODS: From October 2011 to September 2016, a multidisciplinary quality-improvement project was conducted with a plan-do-study-act methodology. Five key drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…16 Through psychoeducation and a biofeedback program, both of which provide therapeutic support and reinforce coping skills, a quality improvement project has demonstrated that hospital LOS and hospital costs can be significantly decreased in SCD patients using a multidisciplinary approach, which included both of these interventions. 17 Patients with SCD are at increased risk for MH conditions given the chronicity of their illness and the distress from acute and/or chronic pain with VOC. Among adult patients with SCD, the prevalence of depressive disorders is estimated to be 5 times higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…16 Through psychoeducation and a biofeedback program, both of which provide therapeutic support and reinforce coping skills, a quality improvement project has demonstrated that hospital LOS and hospital costs can be significantly decreased in SCD patients using a multidisciplinary approach, which included both of these interventions. 17 Patients with SCD are at increased risk for MH conditions given the chronicity of their illness and the distress from acute and/or chronic pain with VOC. Among adult patients with SCD, the prevalence of depressive disorders is estimated to be 5 times higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…It builds on previous work supporting the need for multidisciplinary approaches to care for youth with SCD who experience pain. 33,34 It also provides support for the applicability of Valrie's biopsychosocial model of pediatric pain 14 for understanding the experiences of youth with SCD, and rationale for future studies to investigate the possible moderating role of depression and anxiety symptoms on other functional outcomes in youth with SCD and other pediatric pain populations.…”
Section: Discussionmentioning
confidence: 91%
“…Additional QI projects have demonstrated improved use of other specific pediatric pain management strategies after their inclusion in standard order sets. 19,20 Addressing the issue of time as a barrier may also facilitate acupuncture implementation. Similar to a study of acupuncture implementation in an adult health care setting, 16 our participants discussed that the busy and unpredictable nature of the ED was a barrier to acupuncture usage.…”
Section: Discussionmentioning
confidence: 99%
“…Jain et al 18 found that the addition of specific orders to provider order sets as part of a QI project contributed to successful implementation of jet injection lidocaine for pediatric pain management. Additional QI projects have demonstrated improved use of other specific pediatric pain management strategies after their inclusion in standard order sets 19,20 …”
Section: Discussionmentioning
confidence: 99%